Bone-Derived Modulators That Regulate Brain Function: Emerging Therapeutic Targets for Neurological Disorders - Chen, Hongzhen; Shang, Dewei; Wen, Yuguan; Liang, Chao (Frontiers in Cell and Developmental Biology, 2021)
Bone has traditionally been regarded as a structural organ that supports and protects the various organs of the body. Recent studies suggest that bone also acts as an endocrine organ to regulate whole-body metabolism. Particularly, homeostasis of the bone is shown to be necessary for brain development and function. Abnormal bone metabolism is associated with the onset and progression of neurological disorders. Recently, multiple bone-derived modulators have been shown to participate in brain function and neurological disorders, including osteocalcin, lipocalin 2, and osteopontin, as have bone marrow-derived cells such as mesenchymal stem cells, hematopoietic stem cells, and microglia-like cells. This review summarizes current findings regarding the roles of these bone-derived modulators in the brain, and also follows their involvement in the pathogenesis of neurological disorders. The content of this review may aide in the development of promising therapeutic strategies for neurological disorders via targeting bone.